2022
DOI: 10.1109/tnsre.2022.3157380
|View full text |Cite
|
Sign up to set email alerts
|

Latent Characteristics and Neural Manifold of Brain Functional Network Under Acupuncture

Abstract: Acupuncture can regulate the cognition of brain system, and different manipulations are the keys of realizing the curative effect of acupuncture on human body. Therefore, it is crucial to distinguish and monitor the different acupuncture manipulations automatically. In this brief, in order to enhance the robustness of electroencephalogram (EEG) detection against noise and interference, we propose an acupuncture manipulation detecting framework based on supervised ISOMAP and recurrent neural network (RNN). Prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…The intersection of acupuncture combined with neuroscience and computational science will be an important development in acupuncture for stroke. Several studies [ 74 76 ] have shown that integrating complex central nerves may be the key to acupuncture. Network neuroscience and traditional functional connectivity computing rely on a node-centric network model.…”
Section: Discussionmentioning
confidence: 99%
“…The intersection of acupuncture combined with neuroscience and computational science will be an important development in acupuncture for stroke. Several studies [ 74 76 ] have shown that integrating complex central nerves may be the key to acupuncture. Network neuroscience and traditional functional connectivity computing rely on a node-centric network model.…”
Section: Discussionmentioning
confidence: 99%
“…Acupuncture is a common non-pharmacological treatment for improving gastrointestinal and neurological symptoms (Kwon et al, 2021;Fan et al, 2022a;Yao et al, 2022). Studies have shown that acupuncture can improve gastrointestinal and neurological symptoms while also relieving emotional symptoms (Wang et al, 2022a;Ying-Jia Li et al, 2022). However, it has also been questioned if this is a result of the placebo effects of acupuncture.…”
Section: Introductionmentioning
confidence: 99%
“…Acupuncture is a common non-pharmacological treatment for improving gastrointestinal and neurological symptoms (Kwon et al, 2021;Fan et al, 2022a;Yao et al, 2022). Studies have shown that acupuncture can improve gastrointestinal and neurological symptoms while also relieving emotional symptoms (Wang et al, 2022a;Ying-Jia Li et al, 2022). However, it has also been questioned if this is a result of the placebo effects of acupuncture.…”
Section: Introductionmentioning
confidence: 99%